Effect of Staurosporine on the Intracellular Localization of Hepatitis B Virus Core Protein - Aris Haryanto; Nastiti Wijayanti; Michael Kann (Universitas Gadjah Mada, 2007)
protein is also including in the HBV genome targeting into the nucleus through modulating carboxyl residues byphosphorylation. Nuclear localication Signal (NLS) in HBV core protein is inside the virion structure and it must beunmasked in order to function, perhaps by phosphorylation. Phosphorylation of of HBV core protein in turn couldbegin to alter capsid conformation. Staurosporine is a natural product originally isolated from bacteriumStreptomyces staurosporeus. Staurosporine was discovered to have biological activities ranging from anti-fungal toanti-hypertensive. The interest in these activities resulted in a large investigative effort in chemistry and biology andthe discovery of the potential for anti-cancer treatment. The main biological activity of Staurosporine is the inhibitionof protein kinases through the prevention of ATP binding to the kinase. In the present study, we have studied theintracellular localization of EGFP-Core fusion protein with triple HBV core and SV-40 nuclear localization signal atits carboxyl terminal in presence and absence of Staurosporine. We also to study the effect of Staurosporine treatmenton the intracellular localization of EGFP-Core fusion protein in the hepatocyte cells line of HepG2 cell. Resultsshowed that effect of Staurosporine is prevent the nuclear localization of EGFP-Core fusion protein into nucleusthrough an inhibition of the phosphorylation of core protein. Stauroporine also prevents cell division so that passivetrapping of core protein is inhibited.